An Examination of Differences in Psychological Resilience between Social Anxiety Disorder and Posttraumatic Stress Disorder in the Context of Early Childhood Trauma - Marx, Melanie; Young, Susanne Y.; Harvey, Justin; Rosenstein, David; Seedat, Soraya (Frontiers in Psychology, 2017)
Background Much of the research on anxiety disorders has focused on associated risk factors with less attention paid to factors such as resilience that may mitigate risk or offer protection in the face of psychopathology. Objective This study sought to compare resilience in individuals with posttraumatic stress disorder (PTSD) and social anxiety disorder (SAD) relative to age-, gender- and education- matched individuals with no psychiatric disorder. We further assessed the correlation of resilience scores with childhood trauma, by the type of exposure. Method The sample comprised of 93 participants, 40 with SAD with childhood trauma), 22 with PTSD with childhood trauma, and 31 with no psychiatric disorder (i.e. healthy matched controls). Participants were administered the Mini-International Neuropsychiatric Interview (MINI), Liebowitz Social Anxiety Scale (LSAS), Clinician-Administered PTSD Scale (CAPS), Childhood Trauma Questionnaire - Short Form (CTQ-SF), and the Connor-Davidson Resilience Scale (CD-RISC). The mean age of participants was 34 years (SD = 11). 52 Participants were female (55.9 %) and 54 Caucasian (58.1%). Analysis of variance was used to assess for significant group differences in resilience scores. Non-parametric correlation analyses were conducted for resilience with different types of childhood abuse. Results There were significant differences in resilience between the SAD and PTSD groups with childhood trauma, and controls. Both disorder groups had significantly lower levels of resilience than healthy controls. In the SAD with childhood trauma and PTSD with childhood trauma groups combined, there was a significant positive correlation between resilience and physical neglect. Conclusions Patients who have PTSD and SAD with childhood trauma appear to be significantly less resilient than those with no disorder. Assessing and addressing resilience in these disorders, particularly when childhood trauma is present, may facilitate long-term recovery and warrants further investigation.